ANALISIS SUMBER PERMODALAN YANG DIAKSES OLEH UMKM (STUDI KASUS DI KOTA MALANG) - Khairan Luthfi; Khusnul Ashar (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2014)
This research aims to understand: a. Strategy done by umkm in overcoming limitations capital; b. Capital which institution chosen by lot MSMEs in asking credit .This study took a case study on MSMEs in the Malang City. Research method used is descriptive with qualitative approach phenomenology .This research result having two findings: first , that the owner of MSMEs in Malang City do strategy of capital to the banking institution some others borrow to the cooperative , friends or family as well as some more selling personal belongings .Second , in this research largely informants borrow capital in banking institution namely Bank Rakyat Indonesia. Keyword: MSMEs (UMKM), Capital Resources, Credit